Critical reading competence in family medicine residents - Rojas Carrillo, Esaú; Montoya Trejo, Hector Alejandro; Benites Godínez, Veronica; Velasco González, Luisa Elizabeth; Ramirez Corona, Adriana Gabriela; Benítez Godínez, Eduardo Manuel (Spanish Journal of Medical Education, 2024)
Currently, the specialist doctor has as part of the discharge profile the search, analysis and discussion of information. Reading comprehension is generated after the relationship of the text with the reader and is responsible for building knowledge by relating what has been read and what has been learned. We set out to evaluate the level of critical reading competence in family medicine (MF) residents of the Family Medicine Unit No. 24 (U.M.F. No.24). from the Mexican Social Security Institute (IMSS); To evaluate whether they have critical reading competence, the critical reading evaluation instrument was applied (Campos A et al. 2016). 63% of MF residents presented a medium level of reading comprehension. No statistical significance was found when correlating the variables reading comprehension and gender, and by correlating reading comprehension and age. We conclude that the critical reading competence found in the resident doctors of the U.M.F. No. 24 is of a medium level, being higher than the level found in other studies under similar conditions. It is necessary to establish educational strategies that improve the skills of critical reading of medical articles.